2009
DOI: 10.1186/1742-6405-6-7
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to anti-retroviral therapy among HIV patients in Bangalore, India

Abstract: Introduction: Human Immunodeficiency Virus (HIV) has an estimated prevalence of 0.9% in India (5.2 million). Anti-retroviral drugs (ARV) are the treatments of choice and non-adherence is an important factor in treatment failure and development of resistance, as well as being a powerful predictor of survival. This study assesses adherence to ARV in HIV positive patients in Bangalore, India, a country where only 10% of those who need therapy are receiving it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
103
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(135 citation statements)
references
References 19 publications
30
103
2
Order By: Relevance
“…One Indian cohort study showed that medication adherence increased by 100% in those on less than 5 tablets per day. 16 In contrast to this, previous study of Rakmanina reported that despite having the new regimens, fewer tablets and daily doses, adherence still remains a problem. 25 We also found good adherence with lesser pill burden.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…One Indian cohort study showed that medication adherence increased by 100% in those on less than 5 tablets per day. 16 In contrast to this, previous study of Rakmanina reported that despite having the new regimens, fewer tablets and daily doses, adherence still remains a problem. 25 We also found good adherence with lesser pill burden.…”
Section: Discussionmentioning
confidence: 44%
“…15 Indian cohort study by Beck et al found that duration of treatment for less than 6 months or greater than 10 years was associated with the largest number of missed doses and life time adherence to ART was statistically significantly associated with regular followup attendance. 16 In our study, we did not find statistically significant association between adherence and age, gender and socioeconomic class of caretakers. This was consistent with the study by Venkatesh et al who showed that demographic characteristics, such as age, gender, occupation, and residential status, did not predict treatment adherence.…”
Section: Discussionmentioning
confidence: 49%
“…Alternatively, since the majority of Ugandan youth are unemployed, 17 their less stable economic situation might result in their being unable to meet travel and other costs associated with IPT. [18][19][20][21] Having no education or attaining only primary education was associated with a higher risk of LTFU. An earlier study by Wandwalo and Mørkve demonstrated significant differences in knowledge on TB disease and treatment according to the number of years of school education in Mwanza, Tanzania and its association with poor adherence and LTFU.…”
Section: Discussionmentioning
confidence: 97%
“…The overall male outnumbered the female with male to female ratio 2.79:1 observed in similar other studies like Joge et al, who reported 68.04% male and 31.96% female attendees at an ART center from a rural tertiary care centre of Maharashtra. Another study from an ART center at a tertiary care hospital in south India by Badiger et al reported that 64.4% visitors were male, similarly Wal et al reported 60.9 % male attendees from a tertiary care hospital in north India (9,(12)(13)(14)(15)(16) but in contrast to other studies showing female preponderance, as Tamuno et al reported a distribution of 32.8% of male and 67.2% of female subjects, visiting to a virology clinic at a tertiary care center in western Nigeria, with a male to female ratio of 1:2. 7 This might not be a true representation of female proportion as disease prevalence among both the groups are equal and even female are biologically more vulnerable to HIV/AIDS and more likely to contract infection from their male counterpart.…”
Section: Thementioning
confidence: 99%